Microbiota of vaccinated and non-vaccinated clinically inconspicuous and conspicuous piglets under natural Lawsonia intracellularis infection - Hankel, Julia; Sander, Saara; Muthukumarasamy, Uthayakumar; Strowig, Till; Kamphues, Josef; Jung, Klaus; Visscher, Christian (Frontiers in Veterinary Science, 2022)
Lawsonia (L.) intracellularis is a widespread, economically important bacterium causing the porcine proliferative enteropathy (PPE). In this study, we evaluated intestinal microbiota of naturally exposed L. intracellularis-positive pigs under standardized conditions. To obtain three independent repetitions, 27 L. intracellularis-infected pigs (19.0 ±1.50 kg body weight) from one farm were divided into three groups at an age of seven to eight weeks (nine pigs/group). Pigs were either vaccinated against L. intracellularis via oral drenching on their 21st day of life (attenuated live vaccine) or non-vaccinated and selected according to clinical findings (pigs without deviating fecal consistency or with moderate to soft fecal consistency). Comparison of the clinically inconspicuous piglets that differed regarding their vaccination status showed fewer significant differences in fecal microbiota composition. The vaccination led to an overall enrichment of bacterial species belonging to the order Clostridiales, while species of the genus Collinsella and Prevotella were decreased. Several bacterial species belonging to the order Bacteroidales, mainly of the family Prevotellacecae, often closely matching Prevotella copri differed significantly between non-vaccinated clinically inconspicuous and conspicuous piglets. Whether those bacterial species play a role in mitigating the severity of an L. intracellularis infection remains to be defined.